Electrodeposition of Defect‐Rich Ternary NiCoFe Layered Double Hydroxides: Fine Modulation of Co3+ for Highly Efficient Oxygen Evolution Reaction. Issue 6 (28th December 2021) - Wang, Jiaxin; Sun, Xiaoliang; Hu, Hanbin; Shen, Tianyang; Liu, Guihao; Li, Zewei; Cao, Dongwei; He, Lei; Song, Yu‐Fei
Abstract: The low‐cost, high‐abundance and durable layered double hydroxides (LDHs) have been considered as promising electrocatalysts for oxygen evolution reaction (OER). However, the easy agglomeration of lamellar LDHs in the aqueous phase limits their practical applications. Herein, a series of ternary NiCoFe LDHs were successfully fabricated on nickel foam (NF) via a simple electrodeposition method. The as‐prepared Ni(Co0.5 Fe0.5 )/NF displayed an unique nanoarray structural feature. It showed an OER overpotential of 209 mV at a current density of 10 mA cm −2 in alkaline solution, which was superior to most systems reported so far. As evidenced by the XPS and XAFS results, such excellent performance of Ni(Co0.5 Fe0.5 )/NF was attributed to the higher Co 3+ /Co 2+ ratio and more defects exposed, comparing with Ni(Co0.5 Fe0.5 )‐bulk and Ni(Co0.5 Fe0.5 )‐mono LDHs prepared by conventional coprecipitation method. Furthermore, the ratio of Co to Fe could significantly tune the Co electronic structure of Ni(Cox Fe1‐x )/NF composites ( x =0.25, 0.50 and 0.75) and affect the electrocatalytic activity for OER, in which Ni(Co0.5 Fe0.5 )/NF showed the lowest energy barrier for OER rate‐determining step (from O* to OOH*). This work proposes a facile method to develop high‐efficiency OER electrocatalysts. Abstract : Defective but efficient : The binder‐free Ni(Co0.5 Fe0.5 )/NF, with a unique nanoarray structural feature, was fabricated as a high‐efficiency electrocatalyst towards oxygen evolution reaction (OER). Ni(Co0.5 Fe0.5 )/NF showed the optimized electronic structure and exposed more defects than Ni(Co0.5 Fe0.5 )‐bulk and Ni(Co0.5 Fe0.5 )‐mono prepared by traditional coprecipitation method. As a result, the as‐prepared Ni(Co0.5 Fe0.5 )/NF demonstrated excellent electrochemical activity with an overpotential of 209 mV for OER at 10 mA cm −2 .